PENERAPAN STANDART AKUNTANSI PEMERINTAH BERBASIS AKRUAL DIBADAN LINGKUNGAN HIDUP PROVINSI JAWA TIMUR - Karina Oktavia; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to find out how the East Java Environmental Agency has implemented SAP in financial reporting, the East Java Environmental Protection Agency has fully implemented accruals or is still using cash accruals. This type of research is a type of qualitative research, this research was conducted by taking the object of the Accrual Government Accounting Standard Statement applied in the presentation of financial position to the Office of the Environmental Protection Agency of East Java. According to the research results, in the financial statements of the Environmental Protection Agency of East Java Province, Government Regulation Number 71 of 2010 concerning accrual accounting standards has been implemented, and continues to apply cash basis in accrual accounting. This finding is supported by interviews between researchers. and the Head of Accrual Accounting and Financial Reporting of the East Java Provincial Environmental Agency who stated that the East Java Province Environmental Protection Agency has implemented the SAP accrual basis since the enactment of PP 71/2010. In 2015 it was only started entirely thanks to 5 years of training ... Obstacles in implementing Government Regulation Number 71 of 2010 concerning State Accounting Standards, among others, are related to the mastery of information technology, so it is necessary to have training or seminars for employees such as financial staff so that obstacles to the future can be minimized by increasing the performance of employees at the Environmental Agency.Keywords: PP 71, 2010, SAP accrual method.